IMPLEMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL SOROGAN BERBANTUAN CD PEMBELAJARAN. - Lilik Sulistyo; Priyo Priyo (Jurnal DISPROTEK, 2014)
ABSTRACT Leaning model of sorogan is a traditional learning model used in ??pesantren?. This model is very popular in ??pesantren? community. The aim of this research is to implement the Mathematics Learning with Sorogan Model Supported by CD Learning to know the completeness of achievement of student learning, to know the difference between student learning achievement in mathematics learning using Sorogan Model Supported by CD Learning and Conventional Model, and to know the influence of student activities and the achievement of student learning. In this case, Sorogan Model Supported by CD Learning is an alternative way of learning model, focused on student by giving some opportunities to students to explore, to increase and to get experiences when they face some problems, especially their lessons. Otherwise the matematics teachers are expected to aply this kind of model as one of solution when they have no time to explain material of matematics in the class, particularly inner circle and outer circle of triagle subject, and pay attention to the activities of students to gain the maximal result. The Keywords: Sorogan, Sorogan Supported by CD Learning, Individual Learning. ABSTRAK Pembelajaran model sorogan adalah model pembelajaran tradisional di pesantren. Model pembelajaran ini sangat popular di kalangan (komunitas) pesantren. Tujuan penelitian ini adalah untuk mengimplmentasikan pembelajaran matematika dengan model sorogan berbantuan CD pembelajaran, untuk mengetahui ketuntasan prestasi belajar siswa, untuk mengetahui perbedaan antara prestasi belajar siswa dalam matematika yang menggunakan pembelajaran model sorogan berbantuan CD pembelajaran dengan model konvensional, dan untuk mengetahui pengaruh aktivitas siswa terhadap prestasi belajar siswa. Dalam kasus ini pembelajaran model sorogan berbantuan CD pembelajaran, adalah sebagai model pembelajaran alternative, berpusat pada siswa, memberikan kesempatan pada siswa untuk mengeskplorasi, mengembangkan dan mencari pengalaman ketika mereka menghadapi permasalahan, khususnya yang berkaitan dengan pelajarannya. Sebaliknya guru matematika diharapkan menerapkan jenis pembelajaran model ini sebagai solusi ketika guru menghadapi keterbatasan waktu di dalam kelas. Guru harus jeli/cermat dalam menentukan materi yang memerlukan kehadiran guru dan yang tidak, terutama materi lingkaran dalam dan lingkaran luar segitiga, dan memperhatikan aktivitas siswa untuk memperoleh hasil yang maksimal. Kata Kunci : Sorogan, Sorogan berbatuan CD pembelajaran, belajar mandiri